Adolescent Safety Behaviors and Social Anxiety: Links to Psychosocial Impairments and Functioning with Unfamiliar Peer Confederates. Issue 6 (November 2022) - Okuno, Hide; Rezeppa, Taylor; Raskin, Tabitha; De Los Reyes, Andres
Socially anxious adolescents often endure anxiety-provoking situations using safety behaviors : strategies for minimizing in-the-moment distress (e.g., avoiding eye contact, rehearsing statements before entering a conversation). Studies linking safety behaviors to impaired functioning have largely focused on adults. In a sample of one hundred thirty-four 14 to 15 year-old adolescents, we tested whether levels of safety behaviors among socially anxious adolescents relate to multiple domains of impaired functioning. Adolescents, parents, and research personnel completed survey measures of safety behaviors and social anxiety, adolescents and parents reported about adolescents' evaluative fears and psychosocial impairments, and adolescents participated in a set of tasks designed to simulate social interactions with same-age, unfamiliar peers. Relative to other adolescents in the sample, adolescents high on both safety behaviors and social anxiety displayed greater psychosocial impairments, evaluative fears, and observed social skills deficits within social interactions. These findings have important implications for assessing and treating adolescent social anxiety.